An integrated approach to quantifying uncertainties in the remaining carbon budget - Damon Matthews, H.; Tokarska, Katarzyna B.; Rogelj, Joeri; Smith, Christopher J.; MacDougall, Andrew H.; Haustein, Karsten; Mengis, Nadine; Sippel, Sebastian; Forster, Piers M.; Knutti, Reto (Communications earth & environment, 2021)
The remaining carbon budget quantifies the future CO 2 emissions to limit global warming below a desired level. Carbon budgets are subject to uncertainty in the Transient Climate Response to Cumulative CO 2 Emissions (TCRE), as well as to non-CO 2 climate influences. Here we estimate the TCRE using observational constraints, and integrate the geophysical and socioeconomic uncertainties affecting the distribution of the remaining carbon budget. We estimate a median TCRE of 0.44 °C and 5–95% range of 0.32–0.62 °C per 1000 GtCO 2 emitted. Considering only geophysical uncertainties, our median estimate of the 1.5 °C remaining carbon budget is 440 GtCO 2 from 2020 onwards, with a range of 230–670 GtCO 2 , (for a 67–33% chance of not exceeding the target). Additional socioeconomic uncertainty related to human decisions regarding future non-CO 2 emissions scenarios can further shift the median 1.5 °C remaining carbon budget by ±170 GtCO 2 . Integrating uncertainties using insights from both observations and models narrows the range on the remaining carbon budget for 1.5 °C, as well as the transient climate response to cumulative CO 2 emissions.